Evaluation of monitoring methods in asymptomatic dogs with high serum cystatin C concentrations - IWASA, Naoki (J Vet Med Sci, 2019)
This study evaluated the monitoring methods in asymptomatic dogs with high serum cystatin C (Cys-C) concentrations. Ten dogs with high serum Cys-C were divided into two groups based on the owner’s choice; one receiving clinical pathology-based monitoring at an animal hospital specialised in chronic kidney disease, and the other receiving symptom-based monitoring at home, partly because they showed no clinical symptoms. The dogs that received the clinical pathology-based monitoring led to an early treatment intervention, resulted in a longer survival period than dogs received the symptom-based monitoring (P<0.05). It became clear that early treatment intervention by clinical pathology-based monitoring extends the renal survival period even in asymptomatic dogs with increased serum Cys-C concentrations.